Isolation and purification of lactoferrin from Kazakhstan mare milk (International Journal of Biology and Chemistry, 2020)
The single chemical composition of mare milk, rich in whey proteins is similar to human milk. Lactoferrin is one of the important compounds contained in whey protein fraction, and has multiple biological functions such as antimicrobial and activation of human and animal immune system. Due to its strong antimicrobial activity, lactoferrin has potential pharmaceutical applications. The present work is mainly focused on the isolation and purification of the lactoferrin from mare’s milk. First, the lactoferrin from Kazakhstan mare milk has been purified by gel filtration Sephadex G-100 chromatography in two steps. The column of Sephadex G-100 was eluted with 0.01 M sodium phosphate buffer (pH 6.8). Lactoferrin enriched fractions were detected using UV absorbance at 280 nm and were identified in the first peak. Second, the purity of lactoferrin was checked by 12% SDS–PAGE and the molecular weight of lactoferrin (in the range of 80-82 kDa) was estimated using protein standard, which is recombinant human lactoferrin (expressed in rice, iron saturated, molecular weight 82.4 kDa).